(untitled) (Journal of the College of Education for Women, 2019)
The good preparation for a class of young people is the great importance requirement.This case on the state role to put exceptional philosophy bench form which the entire categorythrough group of experienced educators to prepare different and distinct programs to suitevery specialty of this class. This base of this role can draw upon, including state institutionsneed of young people add urges the mental and physical abilities, scientific and cognitivespecialties and carry it from the levee in the academic certification .And we must not lose thelose sight of the link that pilot projects in which to invest the energies of youth programs andcurricula attractions including incentives .It’s become the subject of job satisfaction of topicsof the interest to behavioral and administrators; this to examine different aspects of the meansand sources satisfaction among employee satisfaction measurement individuals, as well asexamine the causes and dissatisfaction. We’ve been to reach a range of factors that lead tosatisfaction and considered their presence in necessary mainly to achieve the desiredsatisfaction of the employee, plus the loss of these factors lead to development of theemployee in the event of dissatisfaction and therefore reflected on their performance work andcarrying out their duties. Our research is among the young people who need to fill theirdifferent social living pay a lot of them to take a job without competence in the work with adegree to work at different kind of jobs without their desire or ambitions.